In situ generation of silver nanoparticles and nanocomposite films based on electrodeposition of carboxylated chitosan. (15th August 2020) - Pan, Jie; Zhang, Zheng; Zhan, Ziyao; Xiong, Yanfei; Wang, Yifeng; Cao, Kaiyuan; Chen, Yanjun
Graphical abstract: Highlights: A novel method based on biopolymer electrodeposition is used for synthesis of AgNPs. For the first time this work studies the electrodeposition of carboxylated chitosan. Carboxylated chitosan acts as reducing agent, stabilizing agent, and main component. This work provides a simple and controllable means to prepare nanocomposite films. The electrodeposited nanocomposite film with AgNPs shows antibacterial properties. Abstract: Herein, for the first time the electrodeposition of carboxylated chitosan is studied and utilized for the synthesis of silver nanoparticles (AgNPs) and generation of AgNPs/carboxylated chitosan nanocomposite films. Particularly, AgNPs are in situ synthesized on electrodes or substrates during the electrodeposition. Carboxylated chitosan not only acts as the green reducing agent and stabilizing agent for preparing AgNPs, but also serves as the main component in the electrodeposited nanocomposite film. The experimental results indicate that a smooth and homogeneous film is formed on the silver plate after electrodeposition, and the electrodeposited film can be detached from the silver plate as an independent film. The TEM observation and spectroscopic analysis results confirm the existence of AgNPs (the average size of 10 nm) in the nanocomposite film. The nanocomposite films with various shapes can be fabricated by the spatial selectivity of electrodeposition. In addition, the nanocomposite film containing AgNPs shows favorable antibacterial properties.